Upper Jurassic (Malm) Shallow-Water Carbonates in the Western Gorski Kotar Area: Facies and Depositional Environments (Western Croatia) - Josip Tišljar; Ivo Velić (Geologia Croatica, 2010)
Shallow-water carbonates in the Upper Jurassic of the Gorski Kotar were deposited on a carbonate ramp, in beach-barrier island-lagoonal and peritidal environments. In the continuous sequence, more than 900 m thick, several facies have been found: (A) low-energy shallow-water wackestones/mudstones of the Lower Oxfordian, (B) high-energy shallow-water grainstones of the Middle Oxfordian, (C) low-energy, above the fair-weather wave-base packstones of the uppermost Oxfordian and transition to the Kimmeridgian, (D) shallowing-upward/coarsening-upward units formed through progradation of beach-tidal bars or barriers over the peritidal deposits of the Kimmeridgian and the beginning of the Tithonian and (E) peritidal shallowing-upward units capped by storm tidal deposits of the Tithonian and beginning of the Berriasian. Fossil assemblages adapted to the environmental changes: maximum of their abundance, in the number of the taxa, as well as in the number of individuals, corresponds to the high-energy facies B (Oxfordian), while their minimum corresponds to the peritidal shallowing-upward units of facies E (Tithonian).